Telangiectatic Hyperplastic Nodule Associated with Vascular Malformation in a Patient with Chronic Hepatitis B: Radiologic and Pathologic Features - Carrasco, Gonzalo; Besa, Cecilia; Lewis, Sara C.; Kadri, Hena S.; Hiotis, Spiros; Thung, Swan N. (Seminars in Liver Disease, 2013)
Recognizing hepatocellular nodules that cannot be classified as typical for hepatocellular carcinoma, hepatocellular adenoma, or focal nodular hyperplasia is important, especially in a patient with high risk for hepatocellular carcinoma. The authors report a case of a 53-year-old man with chronic hepatitis B, who was referred to the hospital with a liver mass found on routine imaging follow-up. Abdominal ultrasound revealed a 2.4-cm hypoechoic lesion. Contrast computed tomography showed homogeneous arterial enhancement and mild hyperdensity on portal venous phase images. Due to the high risk for hepatocellular carcinoma, the patient underwent laparoscopic left lateral segmentectomy that revealed a 2.2-cm poorly defined red-brown lesion. The nodule was diagnosed as a hypervascular/telangiectatic hyperplastic hepatocellular nodule based on histopathologic findings and immunostaining profile with negative glutamine synthetase, diffuse positive CD34 highlighting hyperplastic endothelial cells along the telangiectatic sinusoids and dilated vascular channels, and CK7 and CK19 reactive normal bile ducts within the lesion.
Keywords: telangiectatic hyperplastic nodule; liver mass; chronic hepatitis B; benign mass; vascular malformation